The felicity of fractals - Abdul Shukor, Shureen Faris; Hussain, Norhuzailin; Mohd Razali, Iskandar Al Khalifah (Universiti Putra Malaysia Press, 2017)
Patterns repeated at different scales like the branches in lungs and neurons, are fractals where simple mathematical rules apply to a vast array of things that look visually complex or chaotic.